Idosos de hoje, atletas olimpicos do passado. - Gomes, Maria Rita Cardoso (2006)
This research has as objective rescues through the aged people's memory that were athletes who had received medals in Olympic Games, memories regarding experiences for them lived and starting from interpretations, to understand the perceptions, feelings and meanings of those experiences lived for them, as well as, their conservation and evocation along the life and in the phase of the aging. To render that study, the professional participation as physiotherapist, the contact with the sport, specifically with Olympic athletes and aged people, they were fundamental and of great motivation for the accomplishment of the same. The accomplishment of the research felt by nature qualitative, being used the oral history, starting from the personal deposition technique for the data s collection from 7 athletes' Olympic medals, in the age group from 63 to 80 years. The results of the study showed that experience of sports was lived intensely by those subjects from the childhood to the adult age, to the point of to constitute a specific and unforgettable moment to them arise to the podium for us to receive their medals, which it will never be forgotten. The reflections of those experiences accompany their life paths, interacting in their decisions. The outstanding meaning of that path took them conserve her alive their glorious memoirs through the rescue along the life and now more frequently in the old age. In that way, they allow to value them the past to the detriment of a present that doesn't answer to their self-esteem needs, love and the valorization of the experiences in family and social level.